A study on Li0.33La0.55TiO3 solid electrolyte with high ionic conductivity and its application in flexible all-solid-state batteries. Issue 26 (25th June 2021) - Tan, Feihu; An, Hua; Li, Ning; Du, Jun; Peng, Zhengchun
Abstract : As flexible all-solid-state batteries are highly safe and light weight, they can be considered as candidates for wearable energy sources. Abstract : As flexible all-solid-state batteries are highly safe and light weight, they can be considered as candidates for wearable energy sources. However, their performance needs to be first improved, which can be done by using highly conductive solid-state electrolytes. Herein, we prepare a crystallized and amorphous LLTO electrolyte through magnetron sputtering and investigate the effect of heat treatment on its ionic conductivity. The maximum ionic conductivity of the electrolyte is 9.44 × 10 −5 S cm −1 at 140 °C. Electrode fracture after multiple cycles is the chief reason for the failure of solid-state batteries. To improve their cycle performance, we use LiNi0.5 Co0.3 Mn0.2 O2 (NCM) with a volume change rate of 5% as the cathode and LTO with a volume change rate of 2% as the anode. A battery with a high output voltage using an internal series is prepared to enhance its application value. The output voltage of a single-layer NCM/LLTO/LTO battery is 2–2.4 V, while that of a two-layer NCM/LLTO/LTO battery can be 4.8 V in series. Owing to the small volume change rate of the electrode, the battery can be cycled up to 500 times, and the capacity of the battery remains at 89.2% of the initial state even after bending.